PELATIHAN PENYUSUNAN BUKU AJAR DIGITAL BERBASIS 3D PAGEFLIP DI SMKN1 PAKU - Nasrah Natsir; Fatmawati Gaffar (Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract. Digital books are a very important requirement in supporting learning in schools, especially in the new normal era like now. The learning process that uses 3D-based digital books can create learning activities that are easy to do and easily accessible. Pageflip is a 3-dimensional application that helps teachers create materials in the form of digital textbooks in all subjects at school. Using the PageFlip application as a medium for compiling 3D-based digital textbooks can make it easier for teachers to convey subject matter to students. Almost all teachers at SMKN 1 Paku have not been able to make 3D-based digital textbooks so that the delivery of material to students is still low. This activity aims to provide training on making digital textbooks using the PageFlip application for teachers at SMKN 1 Paku, Polewali Mandar. Training activities are carried out in several stages, namely socialization, practice, and evaluation. The results of the activity showed that the training participants received increased knowledge and skills related to making 3D-based digital textbooks using the PageFlip application